Size-dependent electrochemical nitrogen reduction catalyzed by monodisperse Au nanoparticles. (1st March 2020) - Chen, Chan; Liang, Cong; Xu, Jun; Wei, Jiankun; Li, Xiangrong; Zheng, Ying; Li, Junrui; Tang, Haolin; Li, Junsheng
Abstract: Electrochemical nitrogen reduction reaction (ENRR) is a mild and environmentally friendly process that can be potentially complementary to the traditional Haber-Bosch process. Development of high-performance ENRR catalysts and understanding of the activity origin of the catalyst are essential for the practical application of ENRR process. Herein, we report the size-dependent ENRR activity of monodisperse Au nanoparticles (NPs) sized ranging from 4 nm to 10 nm. 8 nm Au NPs is found to be an excellent ENRR catalyst with an ammonia production rate and Faradic efficiency of 17.49 μg h −1 mg −1 Au and 5.79%, respectively. The high ENRR performance of 8 nm Au NP is rationalized with DFT studies, which indicate that an optimal proportion of the surface step sites is key to suppressing hydrogen evolution reaction and improving the catalytic activity towards ENRR. The study herein may provide guidelines for tailoring the ENRR catalysis on nanostructured metal catalysts. Graphical abstract: Image 1 Highlights: Monodisperse Au NP is synthesized and used for ENRR. Au NP with a diameter of ∼8 nm shows highest ENRR activity. The 8 nm Au has a balanced fraction of corner site and edge site.